Green buying behavior and the theory of consumption values: A fuzzy-set approach - Gonçalves, Helena Martins (2022)
Using a consumer survey, this study examines whether consumption values can predict green buying behavior. The examination is based on the theory of consumption values and uses the fuzzy-set qualitative comparative analysis. The results show that the functional value is almost always necessary but is not sufficient by itself for predicting green buying. However, three “causal recipes” formed with the functional value are sufficient. These recipes use the emotional, conditional and social values combined individually with the functional value. Other three combinations of consumption values are also sufficient for predicting green buying. In contrast, the absence of the functional value is a sufficient condition for not green buying, as well as three other “causal recipes”. This finding can help marketing managers develop appropriate strategies. Further, this finding supports and clarifies the role of the theory of consumption values by taking advantage of the fuzzy-set qualitative comparative analysis.